Effect of Intermittent Fasting on Glycemic Control in Overweight and Obese Adults: A Meta-analysis of RCTs - Mahmood, Tayyab; Farhan Ullah,; Amin, Hassan; Sadaf, Ammara; Hussain, Yawar; Jyoti,; Abalkariem, Aymen Nasreldin; Maroof, Sobia; Munir, Maria Shafaq; Nipu, Airin Parvin (Indus Journal of Bioscience Research, 2025)
Background: Intermittent fasting (IF) has emerged as a non-pharmacological intervention with potential metabolic benefits, particularly in overweight and obese individuals. However, the effect of IF on glycemic control among non-diabetic adults remains inconsistent across studies. Objective: To evaluate the impact of intermittent fasting on glycemic control, specifically fasting blood glucose and HbA1c levels, in overweight and obese adults through a meta-analysis of randomized controlled trials (RCTs). Methods: A systematic search of PubMed, Scopus, Web of Science, and the Cochrane Library was conducted to identify RCTs published up to April 2024. Studies were included if they involved overweight or obese adults without diabetes, assessed any form of intermittent fasting, and reported glycemic outcomes. Data extraction and risk of bias assessment were performed independently by two reviewers. Standardized mean differences (SMDs) with 95% confidence intervals (Cis) were pooled using a random-effects model. Results:Three RCTs involving various IF regimens, including time-restricted eating and alternate-day fasting, were included. IF significantly improved glycemic control, with a pooled SMD of 1.74 (95% CI: 1.24 to 2.24) in favor of IF over control groups. Subgroup analysis revealed variation based on fasting protocol type. Heterogeneity was high (I² = 82%), and one study exhibited a high risk of attrition bias. Funnel plot analysis showed no significant evidence of publication bias. Conclusion: This meta-analysis supports the use of intermittent fasting as an effective dietary strategy to improve short-term glycemic outcomes in overweight and obese adults. Further high-quality, long-term RCTs are needed to confirm these findings and optimize IF protocols for clinical use.